2016
DOI: 10.1186/s40679-016-0025-y
|View full text |Cite
|
Sign up to set email alerts
|

Deceleration of probe beam by stage bias potential improves resolution of serial block-face scanning electron microscopic images

Abstract: Serial block-face scanning electron microscopy (SBEM) is quickly becoming an important imaging tool to explore three-dimensional biological structure across spatial scales. At probe-beam-electron energies of 2.0 keV or lower, the axial resolution should improve, because there is less primary electron penetration into the block face. More specifically, at these lower energies, the interaction volume is much smaller, and therefore, surface detail is more highly resolved. However, the backscattered electron yield… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 23 publications
0
20
0
Order By: Relevance
“…There is sufficient metal content in the tissue for SEM imaging, as images are captured within small pixel dwell times, and signals are collected from a small interaction volume within a shallow depth. Collectively, all of these changes result in an improved axial resolution and better signal-to-noise ratio 49 , 50 .…”
Section: Discussionmentioning
confidence: 99%
“…There is sufficient metal content in the tissue for SEM imaging, as images are captured within small pixel dwell times, and signals are collected from a small interaction volume within a shallow depth. Collectively, all of these changes result in an improved axial resolution and better signal-to-noise ratio 49 , 50 .…”
Section: Discussionmentioning
confidence: 99%
“…This technique has been known to improve SEM BSE imaging (Ohta et al, 2012). Bouwer et al (Bouwer et al, 2017) observed that applying a negative sample stage bias reduced beam landing energies, reduced sample damage and increased BSE signal-to-noise ratio by accelerating BSE towards the BSE detector above the sample. In conjunction with a special BSE detector they were also able to alter the trajectories of primary and secondary electrons and control beam penetration depth.…”
Section: Imaging and Chargingmentioning
confidence: 99%
“…Faster imaging could also be achieved by increasing signal collection in established thin sections approaches, which would allow for reduced acquisition time while maintaining a sufficient signal to noise ratio (SNR). It has previously been shown that the use of a retarding field increases SNR in SEM (Phifer et al, 2009), but for biological imaging the use of a retarding field has thus far been investigated in detail only for serial blockface scanning EM (SBF-SEM) (Bouwer et al, 2016;Ohta et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…1). The ensuing acceleration results in an increase to the collected signal (Šakić et al, 2011) and-if the detector geometry, landing energy, and potential bias are tuned properlycan be used to filter out secondary electrons (Bouwer et al, 2016). The same signal can in principle then be obtained with a shorter acquisition time.…”
Section: Introductionmentioning
confidence: 99%